Application priority of GSHP systems in the climate conditions of the United States. Issue 1 (2nd January 2019) - Cho, Soolyeon; Ray, Saurabh; Im, Piljae; Honari, Hamed; Ahn, Jonghoon
ABSTRACT: Building energy-performance simulation programs are powerful tools for many aspects of feasibility studies regarding ground source heat pump (GSHP). However, the understanding of the limitations of the energy modelling programs, their capability of predicting energy performance early in the design process, and the complicated functionality of these programs makes the software programs harder to use and less practical. The interactive tool developed in this study seeks to provide analysis information in a straightforward manner that is inexpensive, convenient, and sophisticated. This tool uses an inclusive approach to assess the feasibility of GSHPs by prescreening critical factors such as climate conditions, ground temperatures, energy use, and cost savings. It is interactive and enables the user to do a feasibility analysis with a weighting factor for each feasibility criterion based on the user's preference and interests. The application of the tool explains feasibility scores of 15 representative cities in various climatic conditions across the US. Results for commercial buildings show that the GSHP systems are more feasible in cold and dry, cool and humid, and very cold areas than warm and dry, very hot and humid, and mixed marine areas, and that most feasibility levels are located on good and moderate.